The dynamics of peri-urban land markets in Sub-Saharan Africa: adherence to the virtue of common property vs. quest for individual gain - Wehrmann, Babette (ERDKUNDE, 2008)
Sub-Saharan cities are currently experiencing the world’s highest rate of urbanization. A vast number of people migrate towards the peri-urban areas, changing the use of the land and its ownership, which often implicates a change of the land tenure system as well. Peri-urban land markets are the most dynamic and most diverse in sub-Saharan Africa. The question is whether the different land tenure systems in Africa in the long-run converge towards private property or develop into a diversity of property regimes which might be more divers than elsewhere. The article therefore analyses the changes in property regimes and land tenure systems which are forming current land transaction processes. What types of land tenure systems developed so far? Which property regimes are most in demand? Is there a general trend towards one specific property regime? Are there specific land tenure systems which only exist in sub-Saharan Africa? Based on this analysis, the article aims to identify which land tenure systems and property regimes fit best to meet current needs. Differing from earlier theories such as the Property Rights Doctrine and the Induced Institutional Innovation Hypothesis, the current institutional change in sub-Saharan Africa is neither a straight-forward transition from common to private property nor a self-acting and smooth process. It is rather characterized by insecurity of tenure and numerous conflicts as predicted by Boserup as early as in the 1960s. Although there is a trend towards formal private property, (neo-)customary common property provides for numerous advantages which are appreciated not only by the poor. Common property being so appreciated in sub-Saharan Africa, the author also investigates why over centuries it has been neglected by mainstream theories.